Dopamine triggers TOR signaling cascade to drive biomass and astaxanthin hyperaccumulation in Haematococcus lacustris under coordinated salinity and gradient light stress - Shiyu Lin; Qingwei Wang; Raoqiong Che; Qingqing Li; Chunli Yu; Min Yang; Lifang Li; Penghua Gao; Ying Qi; Feiyan Huang; Xiang Wang; Yongteng Zhao; et al. (Bioresource Technology, 2026)

Effects of Aluminum Salts on Bacterial Community in Epiphytic Biofilms on Vallisneria Natans Leaves: Characteristics of Nitrogen and Phosphorus Fractions and Bacterial Community Composition - Xue Peng; Xinyi Zhang; Shuxian Zhang; Qingwei Lin; Haokun Zhang; Xiaowen Zhang; Yi Zhang; Steven Jing-Liang Xu; Fred Wang-Fat Lee; Nora Fung-yee Tam; Zhenbin Wu; Biyun Liu (Water, Air, & Soil Pollution, 2026)

pH-responsive conformational variations regulate the emulsifying properties of Coprinus comatus protein-polysaccharide complex - Qingwei Lin; Yanyu Hu; Xu Chen; Xixi Cai; Shaoyun Wang (Food Research International, 2026)

Phosphorus-driven enhancement of microalgal growth, lipid biosynthesis, and nutrient removal efficiency in Monoraphidium sp. QLZ-3: Implications for biofuel production and high‑phosphorus wastewater treatment - Shiyu Lin; Jinkun You; Yongteng Zhao; Qingwei Wang; Ying Qi; Feiyan Huang; Xuya Yu; Lei Yu (Algal Research, 2026)

Unveiling the submerged iceberg of semi-volatile organic pollutants in surface water across the Yangtze River Basin - Quanzhen Liu; Xiong Xu; Mengru Yang; Qingwei Bu; Yongchang Xie; Lihua Lin; Lu Bai; Donghong Wang (Water Research, 2026)

Enhanced photothermal combustion efficiency of propane in the presence of SO2 over Mo-doped Pt/WO3 catalyst: Rational utilization of Ptδ+-(SO4)δ- - Lijing Han; Huimin Chai; Jinliang Lin; Kaiting Chen; Qingwei Li; Qiuhong Zhou; Jun Ye; Hai Liu; Xinyu Han; Zeshu Zhang; Yibo Zhang (Journal of Environmental Chemical Engineering, 2025)

Floodplain hydrodynamics and connectivity in a natural compound channel during unsteady flow events - Jiaming Liu; Yang Xiao; Saiyu Yuan; Taotao Zhang; Qingwei Lin; Kang Yuan; Ruiqi Wang; Carlo Gualtieri (Journal of Hydrology, 2025)

Multistage crystallization strategy for simultaneous recovery of NH₄SCN and (NH₄)₂SO₄ from hazardous desulfurization residues: Process optimization and techno-economic assessment - Junyun Cheng; Chenruobing Zhang; Jie Lin; Yeqiu Zhao; Yu Huang; Meiqing Shi; Zhiqi Zhu; Liyuan Chai; Xu Yan; Qingwei Wang (Process Safety and Environmental Protection, 2025)

Water quality prediction at large-Scale: Systematic assessment of decomposition-deep learning models - Jiahui Shi; Lixiao Ni; Jiaming Liu; Hui Chen; Yushen Ma; Yi Zhang; Qingwei Lin; Zhen Zhang; Hang Xu; Yiping Li (Journal of Cleaner Production, 2025)

Growth behavior of heavy metal sulfide particles: A comparison between gas-liquid and liquid-liquid sulfidation - Chunxue Li; Meiqing Shi; Qingzhu Li; Jiahui Wu; Xu Yan; Qingwei Wang; Zhang Lin; Liyuan Chai (Journal of Environmental Sciences, 2025)

Effects of green space exposure on acute respiratory illness in community-dwelling older people: A prospective cohort study - Qingwei Zhong; Lefei Han; Xinyue Ye; Lin Yang (Landscape and Urban Planning, 2025)

Understanding the deactivation factors for pre-classification of spent SCR catalysts treatment - Qiuyun Huang; Ruiying Hu; Zhen Wu; Xueming Liu; Qingwei Wang; Hao Chen; Fenghua Shen; Wenchao Zhang; Zhang Lin (Chemical Engineering Journal, 2025)

One-step in-situ construction of Cu2O/Ti3C2Tx@TiO2 enabling interfacial photothermal reforming of MeOH/H2O into H2 - Baofang Zhang; Ziyu Zengcai; Wenting Lin; Wenjie Gu; Dizhou Lou; Ruixi Luo; Qingwei Meng; Yunhong Pi; Tiejun Wang (Fuel, 2025)

Homemade isothermal amplification-initiated Cas14a assay for rapid quantitative detection of aquatic RNA virus gene with no PAM - Xiufen Yang; Lin Lu; Yanchi Luo; Qingwei Wang; Jianing Wang; Yihua Ren; Yuwei Wu; Masoud Negahdary; Khaydar E. Yunusov; Sherzod A. Yuldoshov; Abdushkur A. Sarimsakov; Haimei Mao; et al. (Aquaculture, 2025)

Clinical efficacy and safety of vortioxetine as an adjuvant drug for patients with bipolar depression - Chunxiao Dai; Yaoyang Fu; Xuanwei Li; Meihua Lin; Yinbo Li; Xiao Li; Keke Huang; Chengcheng Zhou; Jian Xie; Qingwei Zhao; Shaohua Hu (Journal of Zhejiang University-SCIENCE B, 2025)

Cross-domain few-shot semantic segmentation for the astronaut work environment - Qingwei Sun; Jiangang Chao; Wanhong Lin (Advances in Space Research, 2024)

Biochar affects soil properties over 1 m depth in an alkaline soil of north China Plain - Xiongxiong Bai; Jiao Tang; Qingwei Lin (Journal of Environmental Management, 2024)

The long-term effects of norgestrel on the reproductive and thyroid systems in adult zebrafish at environmentally relevant concentrations - Shuyan Mai; Yan-Qiu Liang; Shuhui Zhou; Hongjie Lin; Zhongdian Dong; Chang-Gui Pan; Qingwei Kong; Shaoshuai Wang; Shiqing Wang; Zhong Lin; Liping Hou (Aquatic Toxicology, 2024)

Recovering element sulfur from sulfur-containing waste through a pressure induced melting-crystallization method: Optimization using response surface methodology - Fanyun Chen; Chen Tian; Xuelin Pan; Qingshan Gao; Qingwei Wang; Liyuan Chai; Zhang Lin (Chemical Engineering Journal, 2024)

Coupled aero-servo-elastic method for floating offshore wind turbine wake analysis - Lin Yang; Kangping Liao; Qingwei Ma; Abbas Khayyer; Hanbing Sun (Ocean Engineering, 2024)

Corrigendum to “Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study” [Water Research 252 (2024) 12191] - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

Unraveling the ecological mechanisms of Aluminum on microbial community succession in epiphytic biofilms on Vallisneria natans leaves: Novel insights from microbial interactions - Xue Peng; Xiaowen Zhang; Zhuxi Li; Shuxian Zhang; Xinyi Zhang; Haokun Zhang; Qingwei Lin; Xia Li; Lu Zhang; Fangjie Ge; Zhenbin Wu; Biyun Liu (Journal of Hazardous Materials, 2024)

MazF-rolling circle amplification combined MALDI-TOF MS for site-specific detection of N6-methyladenosine RNA - Guobin Han; Qiuyuan Lin; Jia Yi; Qian Lyu; Qingwei Ma; Liang Qiao (Analytica Chimica Acta, 2024)

Unveiling the role of pore characteristics in sludge dewatering: Visualization by Nano-CT and micromodel study - Yue Wang; Jiawei Li; Fan Feng; Caiyan Qu; Chongjian Tang; Qingwei Wang; Wenchao Zhang; Xu Yan; Zhang Lin (Water Research, 2024)

The response of rhubarb to smut infection is revealed through a comparative transcriptome and metabolome study - Shuangshuang Zhou; Ya Lin; Yu Cai; Linfang Li; Xiaohui Yao; Kuan Sun; Qin Song; Qingwei Zhang (Planta, 2024)

Fabrication of bimetallic MOF with 2D nanosheets structure and rich active sites for enhanced removal of organic pollutants by activation of peroxymonosulfate - Ning Li; Huanxuan Li; Ran Ji; Sihang Lin; Chen Xu; Jingang Huang; Qingwei Zhou; Shuguang Lyu; Feng Li; Junhong Tang (Journal of Environmental Chemical Engineering, 2023)

Engineering highly efficient NIR-II FRET platform for Background-Free homogeneous detection of SARS-CoV-2 neutralizing antibodies in whole blood - Lei Zhao; Qingwei Song; Weikang Mai; Min Deng; Yu Lei; Lu Chen; Weiya Kong; Lei Zhang; Lin Zhang; Yantao Li; Huiru Ye; Yiru Qin; et al. (Chemical Engineering Journal, 2023)

The Impact of Scour on Laterally Loaded Piles Bored and Socketed in Marine Clay - Chentao Li; Yang Xiao; Jieqing Liu; Qingwei Lin; Taotao Zhang; Jiaming Liu (Journal of Marine Science and Engineering, 2022)
The majority of long-span bridges and offshore construction in deep water are supported by bored pile foundations. Pile foundations under water will be susceptible to scour, which will pose a significant danger to their safe operation. A three-dimensional finite element (FE) numerical analysis was conducted to examine the influence of scour on the responses of laterally loaded drilled piles in marine clays. First, the FE numerical model was calibrated using field test data of a drilled pile that did not include scour in soft marine clay. The findings of numerical modeling reveal that scour decreases the ultimate lateral capacity of socketed drilled piles, with the percentage of reduction being strongly related to scour types and depth, but moderately related to scour hole width and slope angle. Finally, a semi-empirical formula for calculating the effects of scour on the lateral capacity of socketed drilled piles following scour is presented. This method may be utilized fast and effectively to calculate scour’s effects.

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

Formation of high crystalline LDH sludge for removing Cu and Zn from wastewater by controlled double-jet precipitation - Lanyan Wu; Bing Peng; Qingzhu Li; Qingwei Wang; Xu Yan; Qiuhong Lin; Chunlei Ji (Environmental Science and Pollution Research, 2019)

Analysis of miRNA-seq combined with gene expression profile reveals the complexity of salinity stress response in Oryza sativa - Qingwei Wang; Tianlong Geng; Shuhua Zhu; Rui Li; Yongao Tong; Shenghua Wang; Fang Chen; Lin Tang; Yang He (Acta Physiologiae Plantarum, 2017)

Formation mechanisms of the alpine Erman’s birch (Betula ermanii) treeline on Changbai Mountain in Northeast China - Dapao Yu; Qingwei Wang; Jiaqing Liu; Wangming Zhou; Lin Qi; Xiaoyu Wang; Li Zhou; Limin Dai (Trees, 2014)

Oxygen Metabolism in Ischemic Stroke Using Magnetic Resonance Imaging - Hongyu An; Qingwei Liu; Yasheng Chen; Katie D. Vo; Andria L. Ford; Jin-Moo Lee; Weili Lin (Translational Stroke Research, 2012)